Emotional reactivity and perseveration: Independent dimensions of trait positive and negative affectivity and differential associations with psychological distress - Boyes, M.; Carmody, T.; Clarke, P.; Hasking, Penelope (Pergamon Press, 2017)
Background: Theoretically, two types of emotional responding could underlie individual differences in trait affect: 1) a disposition reflecting increased probability of experiencing positive or negative emotions (emotional reactivity), and 2) a disposition to experience prolonged emotional reactions once elicited (emotional perseveration). We developed a measure of these dimensions and investigated whether emotional reactivity and perseveration 1) account for unique variance in trait affect, and 2) are differentially associated with symptoms of psychological distress. Method: In Study 1, participants (T1: n = 90; T2: n = 51) completed the Positive and Negative Affect Schedule (PANAS) and the Emotional Reactivity and Perseveration Scale (ERPS, adapted from the PANAS). In study 2, participants (n = 228) completed the PANAS, ERPS, and Depression Anxiety Stress Scales. Results: Study 1 established the basic psychometric properties of the ERPS and demonstrated that emotional reactivity and perseveration accounted for unique variance in trait positive and negative effect. Study 2 confirmed these findings and established that emotional reactivity and perseveration are differentially associated with depression, anxiety, and stress scores. Conclusion: Emotional reactivity and perseveration represent independent dimensions of trait affect. Considering these dimension in future research could further the understanding of both normal emotional responding and emotional vulnerability.